Natural rubber graft copolymer synthesis - a review - Wan Abdul Rahman , Wan Aizan (Faculty of Chemical & Natural Resources Engineering, 1992)
Interest in modifying natural rubber has dampened after the emergence and development of the plastics and synthetic rubber industries and the bottom fell out of the natural rubber market. The current modification is being epoxide and thermoplastic natural rubber (TPNR).